PCB plasma level in different occupational groups in Iran - Eftekhari, Sahar; Aminian, Omid; Esser, André; Schettgen, Thomas; Kaifie, Andrea; Felten, Michael; Kraus, Thomas; Moinfar, Zeinab (Toxicology and Industrial Health, 2021)
Despite the ban of polychlorinated biphenyls (PCBs) some decades ago, concerns regarding their adverse health effects are continuing, because the workers employed for installation and repair of electrical equipment may be still exposed to PCBs. This study aimed to assess serum PCBs levels in workers in different industries. To do this, we determined the serum concentrations of 9 non-dioxin-like PCBs and 12 dioxin-like PCBs in 147 workers from seven occupational groups and 35 housewives. An electrical distribution company, paint manufacturer, and pesticide manufacturer were categorized as high probability exposure jobs, whereas turning and casting operations, polymer plastic manufacturing, professional driving, and office work were categorized as low probability exposure jobs. In addition, the average of PCB 138, 153, and 180 and PCB sums were observed to be significantly higher in paint manufacture workers compared to the another groups. In addition, the average PCB 118 level was higher in electrical distribution workers and housewives. Following the adjustment for age, blood lipid, residency place, and seafood in the regression model, the association of PCB 118 in electrical distribution workers and PCB 153 in paint manufacture workers remained significant. The results of this study served as further support for the hypothesis for an occupational basis for bioaccumulation of some PCB types. However, the plasma levels of almost all PCB congeners in Iran were found to be lower than many other countries.
CRIS-Team Scopus Importer:2023-09-25
Keywords: biomonitoring; electrical distribution; Iran; occupational exposure; paint manufacture; Polychlorinated biphenyls (PCBs)